Penggunaan Media Big Book untuk Meingkatan Kemampuan Membaca Permulaan Anak Tunarungu Kelas Dasar II SDLB Negeri Ternate - Asma Asma (Peneliti.net, 2020)
The purpose of this study was to determine whether the Big Book media can improve the ability to read beginning in elementary grade II deaf children in SDLB Negeri Ternate. The research method used in this research is the single subject experimental method or Single Subject Research (SSR). The design used in this research is the A-B-A design, which consists of baseline-1, intervention, and baseline-2 phases. The subject in this study was a child with hearing impairment in elementary grade II at SDLB Negeri Ternate. Based on the results of data analysis and discussion of research results, it can be concluded that Big Book media can improve the beginning reading ability of elementary class II deaf children in SDLB Negeri Ternate. This is indicated by the overlap of data in the analysis between conditions A1 / B and B / A2 at 0%, which means that the smaller the percentage of overlap, the greater the influence on the target behavior. This was supported by the increase in baseline reading scores during the baseline-1, intervention, and baseline-2 phases. With these results, it shows that Big Book media can improve the beginning reading skills of elementary class II deaf children at SDLB Negeri Ternate